2018
DOI: 10.1007/s10493-018-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: The first authenticated record of the pangolin tick Amblyomma javanense (Acari: Ixodidae) in Singapore, with notes on its biology and conservation

Abstract: Due to an unfortunate turn of events, the surname of the third author appeared incorrectly in the original publication as it should have read Douay. The original article has been corrected, and the proper representation of the authors' names and their affiliation is also listed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, the pangolins we observed are asymptomatic. The previous studies have observed Amblyomma javanense, a tick from the family Ixodidae, feeding on pangolins and other hosts such as water monitor lizards (Varanus salvator) and wild boar (Sus scrofa L.) [23][24][25][26] and thus can be a vector for circulating Babesia spp. in the pangolin population and other hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pangolins we observed are asymptomatic. The previous studies have observed Amblyomma javanense, a tick from the family Ixodidae, feeding on pangolins and other hosts such as water monitor lizards (Varanus salvator) and wild boar (Sus scrofa L.) [23][24][25][26] and thus can be a vector for circulating Babesia spp. in the pangolin population and other hosts.…”
Section: Discussionmentioning
confidence: 99%